Wzmocniona współpraca w Unii Europejskiej po raz trzeci. Postępujące zróżnicowanie integracji oraz rozwój wzmocnionej współpracy i jej znaczenie dla funkcjonowania UE - Kubin, Tomasz (Rocznik Integracji Europejskiej, 2015)
The Treaty of Amsterdam introduced the provisions concerning the establishment o f enhanced cooperation in the European Union that were not been applied for over a decade after its signing. The first time it happened was in 2010. The EU Council made a decision to establish such a form o f cooperation on two more occasions - most recently in 2013, on a financial transaction tax (FTT). In this way, the enhanced cooperation has become a permanent and increasingly important form of cooperation within the EU, helping to deepen the diversity of integration in the Union. The paper aims to show the importance of the development of enhanced cooperation, including in particular the subsequent decision to implement enhanced cooperation in the area of FTT, for the functioning of the EU. To outline the context of this problem, the legal basis for enhanced cooperation contained in the Treaties and the examples of integration diversity before 2010 are synthetically indicated; the actions and decisions taken by the states and the EU institutions in connection with the economic crisis, which also affected the diversity of integration in the EU, are listed; and the two first cases of enhanced cooperation are briefly described. The most important conclusions are contained in the final part of the study.